Influence of block-out on retentive force of thermoplastic resin clasps: an in vitro experimental and finite element analysis. Issue 3 (July 2019) - Yamazaki, Toshiki; Murakami, Natsuko; Suzuki, Shizuka; Handa, Kazuyuki; Yatabe, Masaru; Takahashi, Hidekazu; Wakabayashi, Noriyuki
Abstract: Purpose: The purpose of this study was to determine the effect of block-out preparation, used to eliminate the undercut area, on the retentive force and stress distribution of resin clasps. Methods: A total of 72 polyester and polyamide resin clasps were fabricated on a premolar abutment crown following six block-out preparations. A combination of two types of vertical block-outs and three types of horizontal block-outs (on the missing side) was used on the abutment tooth. Each clasp was subjected to an in vitro removal test using a universal testing machine. The retentive force and traces of the clasp on the abutment tooth were recorded and analyzed with one-way analysis of variance and post hoc comparisons ( α = 0.05). Non-linear finite element analysis was performed to assess the stress distributions of the resin clasps. Results: Resin clasps with a vertical block-out of 0.75 mm undercut showed significantly higher retentive force than those with the 0.5 mm undercut. Resin clasps with horizontal block-out showed significantly lower retentive force than those without horizontal block-out. There was no significant difference between the two thermoplastic resins. The maximum first principal stress of the resin clasp was concentrated under the shoulder of the clasp and strongly influenced by the width of horizontal block-out in the finite element analysis. Conclusions: This in vitro experiment suggested that a horizontal block-out is necessary even for a 0.5-mm undercut. The design of the resin clasp should be considered from two aspects: retentive force and deformation risk.